2021
DOI: 10.1002/adhm.202100839
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Hydrogel Tubes with Poly(ɛ‐Caprolactone) Sheaths for Small‐Diameter Vascular Grafts

Abstract: Small-diameter vascular grafts (inner diameter < 6 mm) are useful in treating cardiovascular diseases. The off-the-shelf small-diameter vascular grafts for clinical applications remain a great limitation owing to their thrombogenicity or intimal hyperplasia. Herein, bilayer anticoagulant hydrogel tubes with poly( -caprolactone) (PCL) sheaths are prepared by freeze-thawing and electrospinning, which contain nanofibrillated cellulose (NFC)/poly(vinyl alcohol) (PVA)-heparin/poly-L-lysine nanoparticles tube as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 82 publications
(17 reference statements)
0
27
0
Order By: Relevance
“… 173 It has been reported that PVA demonstrated low platelet adhesion and low thrombin generation time. 174 However, PVA hydrogel for a vascular graft showed that the modified PVA with fibronectin, RGDS peptide, cyclicRGD (cRGD) peptide, and heparin showed platelet adhesion similar to that of ePTFE and unmodified PVA. However, the modified PVA had an increased endothelial cell proliferation.…”
Section: Strategies To Prevent Intimal Hyperplasia In Vascular Graftsmentioning
confidence: 99%
See 1 more Smart Citation
“… 173 It has been reported that PVA demonstrated low platelet adhesion and low thrombin generation time. 174 However, PVA hydrogel for a vascular graft showed that the modified PVA with fibronectin, RGDS peptide, cyclicRGD (cRGD) peptide, and heparin showed platelet adhesion similar to that of ePTFE and unmodified PVA. However, the modified PVA had an increased endothelial cell proliferation.…”
Section: Strategies To Prevent Intimal Hyperplasia In Vascular Graftsmentioning
confidence: 99%
“…However, the modified PVA had an increased endothelial cell proliferation. 174 Endothelialization of PVA surfaces is a major limitation and can be overcome by modifying biochemical and topographical cues to improve its bioactivity without compromising hemocompatibility. Polypeptides such as fibronectin, peptide (RGDS and cRGD), and lysine, as well as the anticoagulant heparin may be used for this purpose.…”
Section: Strategies To Prevent Intimal Hyperplasia In Vascular Graftsmentioning
confidence: 99%
“…Inflammation and foreign-body responses of MFVs were investigated via subcutaneous implantation. 68,69 After 5, 10 and 30 days of implantation, the implanted MFV was removed out and used for hematoxylin and eosin (H&E) staining and histological analysis (CD 68 staining) (Fig. 5b).…”
Section: Resultsmentioning
confidence: 99%
“…PVA is however a mechanically weak polymer. The mechanical properties of PVA can be strengthened with the addition of nanocellulose, , while its bioactivity can be improved by the incorporation of natural polymers or bioceramics. …”
Section: Categories Of Synthetic Polymers For Tissue Engineeringmentioning
confidence: 99%
“…PCL is the dominating polymer among the newer scaffolds that are explored for the regeneration of vessels ,,,, and is preferred because of its mechanical properties (ductility), suturability, and absence of graft dilation. To compensate for its slow degradation rate, it is combined with other polymers.…”
Section: Design Aspects Polymer Selection and Latest Advancesmentioning
confidence: 99%